Beau Lines Due to Docataxel Treatment: Case Report - Coskun, Basak Kandi; Turgut, Dilara; Saral, Yunus (Deri Zuhrevi Hastaliklar Dernegi, 2006)
Beau's lines are transverse furrows that begin in the damage matrix and progress distally as the nail grow. One or more line can be found on nail plaque. Docetaxel is a chemotherapy drug which is used for breast and lung cancer. Here we present a patient who has Beau's lines on all of the nail plaque due to docetaxel.
Keywords: Docetaxel; Beau's lines